Starting Child Care: Child Care 2 - Suzanna Smith (EDIS, 2012)
“Many parents have suffered the heart-wrenching moment of dropping their baby at a new childcare setting, only to have them cling and cry. If your child is starting child care, you can help make the transition easier by following a few guidelines from child development experts to help you and your child prepare for this change.” This 2-page Family Album Radio transcript was written by Suzanna Smith, and published by the UF Department of Family, Youth and Community Sciences, July 2012.